The Role of Local Regulations in Enforcing Waste Disposal Laws in Mangrove Ecotourism Destinations - Evi febri sartika; Agung Edy Wibowo; Sri Turatmiyah; Dwi Afni Maileni; Rizki Tri Anugrah Bhakti (Simbur Cahaya, 2026)
Mangrove forest tourism has emerged as a natural destination, increasingly visited by people seeking a refreshing atmosphere to relieve work-related stress. As an ecotourism site, the mangrove ecosystem requires strict preservation efforts to ensure its sustainability. However, the limited carrying capacity and inadequate supporting facilities pose significant challenges, as irresponsible human behaviour, particularly through improper waste disposal, can accelerate environmental degradation. Indiscriminate waste dumping not only threatens the natural beauty of the mangrove forest but also disrupts the ecological balance, leading to long-term environmental damage, including soil and water pollution, a decline in biodiversity, and weakened natural coastal protection. These negative impacts ultimately undermine the very essence of ecotourism, which is to promote harmony between humans and nature. Although Indonesia has established a legal framework through national waste management regulations, their effectiveness relies heavily on localised law enforcement and community compliance. Strengthening the role of local regulations and ensuring their enforcement in Batam, particularly in the Nongsa mangrove tourism area, is therefore crucial to maintaining order, ensuring visitor safety, and protecting natural resources. The existence of clear and enforceable local regulations can serve as a preventive measure, deterring harmful behaviour while encouraging environmentally responsible practices. Moreover, such enforcement contributes significantly to ecological sustainability by fostering awareness among visitors and local communities about the importance of preserving mangroves as a buffer against climate change and coastal erosion. This research highlights the urgency of legal measures to address improper waste disposal in mangrove ecotourism destinations, emphasising the strategic role of local regulations in achieving sustainable tourism. Ultimately, legal enforcement serves not only as a deterrent against environmental violations but also as an instrument to safeguard ecological integrity for present and future generations